2021
DOI: 10.1002/ptr.7236
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic monophenols from cinnamon bark act as proteasome inhibitors by upregulating ER stress, suppressing FoxM1 expression, and inducing apoptosis in prostate cancer cells

Abstract: Cinnamon contains bioactive substances with diverse medicinal properties. We investigated the anticancer potential of abundant monophenols from cinnamon, namely, cinnamaldehyde, cinnamic acid, and eugenol, by hypothesizing that they possess proteasome inhibitory activities capable of suppressing cancer cell proliferation and inducing apoptosis. This hypothesis was tested by evaluating proteasome inhibitory activities of the compounds, and assessing downstream molecular and cellular events that are known to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Moreover, apoptosis occurred through the inhibition of 26S proteasome activity, the induction of a dose-dependent increase in caspase-3 activity, a decrease in Akt protein levels and a decrease in anti-apoptotic (Survivin and XIAP) and angiogenic (VEGF and VEGF receptor) gene markers' expression in both cancer cells lines [110]. An HPLC analysis of this aqueous cinnamon extract revealed the presence of high amounts of cinnamaldehyde [86].…”
Section: Cinnamonmentioning
confidence: 93%
See 2 more Smart Citations
“…Moreover, apoptosis occurred through the inhibition of 26S proteasome activity, the induction of a dose-dependent increase in caspase-3 activity, a decrease in Akt protein levels and a decrease in anti-apoptotic (Survivin and XIAP) and angiogenic (VEGF and VEGF receptor) gene markers' expression in both cancer cells lines [110]. An HPLC analysis of this aqueous cinnamon extract revealed the presence of high amounts of cinnamaldehyde [86].…”
Section: Cinnamonmentioning
confidence: 93%
“…In addition, cinnamon compounds downregulated the expression of angiogenic factors (VEGF and VEGFR), acting as antiangiogenic agents. The treatment of tumor cells with cinnamon compounds also led to a dose-dependent decrease in cell viability with IC 50 values of 14.3 µM for cinnamaldehyde, 73.2 µM for eugenol and 6.2 µM for cinnamic acid [86]. Eugenol also inhibits the growth of DU145 cells [90].…”
Section: Cinnamonmentioning
confidence: 99%
See 1 more Smart Citation
“…The proteasome is an anticancer target, and proteasome inhibition can promote apoptosis and inhibit tumor growth ( 78 , 79 ). Gopalakrishnan and Ismail ( 80 ) found that cinnamon compounds can inhibit the activity of the proteasome, leading to the accumulation of p27 protein, thereby inhibiting the proliferation of prostate cancer cells. Meanwhile, cinnamon compounds also lead to downregulation of vascular endothelial growth factor A (VEGFA) and VEGF receptor, thereby inhibiting the angiogenic capability of tumor cells.…”
Section: Antitumor Effects Of Ca In Different Types Of Cancermentioning
confidence: 99%
“…By contrast, FOXM1 knockdown induces prostate cancer cell apoptosis (26,48). In addition, FOXM1 inhibition by miRNAs (e.g., miR-193b) or chemical compounds [e.g., forkhead domain inhibitory compound-6 (FDI-6), niclosamide, siomycin A, SR9009, morusin, cinnamaldehyde, cinnamic acid and eugenol] was reported to induce apoptosis (23,26,27,33,50,52,53).…”
Section: Apoptosis and Autophagymentioning
confidence: 99%